Analisis Kebutuhan Zona Selamat Sekolah (Zoss) Di Ruas Jalan Taman Siswa, Sekaran, Kec. Gunungpati, Kota Semarang - Farhan Sholahudin Sholahudin; Endah Kanti Pangestuti; Rini Kusumawardhani; Untoro Nugroho (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2023)
The high pedestrian activity on the Taman Siswa Road Section raises the potential for traffic accidents given the high volume of traffic and vehicle speeds, especially during peak hour when going to and from school. The purpose of this study was to analyze the need for pedestrian facilities, the Safe School Zone (ZoSS) on the Taman Siswa Road Section, especially in the school area, SD N Sekaran 1, SD N Sekaran 2 and MI Roudlotul Huda. The research method used to determine the need for pedestrian facilities is by surveying traffic volume, vehicle speed, volume and movement of pedestrians which were analyzed based on MKJI 1997 and PV2. From the results of the analysis, the traffic volume is 1,006 smp/hour during peak hours at 06.30-07.30 WIB. With the value of the road capacity analysis of 1,304.331 smp. So that the road service level of 0.771 is obtained, level C with an average speed on the Taman Siswa Road Section of 37.065 km/hour. For the analysis of the need for pedestrian crossing facilities at SD N Sekaran 1, SD N Sekaran 2, and MI Roudlotul Huda it shows a PV2 value = > 2 x 108, which means that in these locations it is recommended to provide pedestrian crossing facilities in the form of zebra crossing with protection. For the facilities needed by pedestrians, it is recommended to provide sidewalks with a width of 3 meters. At all school locations that have carried out the Z test on speed analysis, analysis of pedestrian behavior when crossing, analysis of introductory behavior, it is concluded that the road is not safe. For this reason, it is necessary to need road equipment facilities in the form of a Safe School Zone (ZoSS). The results of this study are expected to be useful for road users, especially pedestrians in the school area, so that when walking along and crossing the road it provides security and safety for pedestrians.